Therapeutic potential of natural compounds for treatment of chronic obstructive pulmonary disease: Current status and future perspective - Sanjeev Kumar Sahu; MD Musarraf Rain; Manish Vyas (Elsevier, 2024)
Chronic obstructive pulmonary disease (COPD) is a lung disease which is the third most common cause of premature death globally. Inhaling dangerous gases, cigarette smoking, and exposure to pollution are the main factors contributing to the development of COPD. These factors may harm lung tissue and create COPD causes. Increased synthesis of inflammatory mediators and proteases because of cigarette smoking exposure to transcriptional factors. Dysfunction of mitochondria essential part to lead and development of several human illnesses, such as chronic obstructive pulmonary disease. Alpha-1 antitrypsin deficiency boosts neutrophil elastase activity, which promotes tissue deterioration and emphysema (particularly in smokers because cigarette smoke also boosts protease activity). In this review, we discussed all these factors and summarized the conventional drug currently present for the treatment of COPD. In addition, we also focused on various natural compounds categorized under the flavonoids, polyphenols, alkaloids, glycosides and marine compounds which were reported for the effective treatment of COPD.